Effect of narrative nursing combined with Traditional Chinese Medicine foot soaking and auricular acupoint pressing in the treatment of post-stroke sleep disorder (叙事护理联合中药泡足和耳穴贴压治疗脑卒中后睡眠障碍的效果观察) - CHAI Jingjing (柴晶晶); MENG Xiangnan (孟祥楠) (中西医结合护理)
Objective To investigate the effect of narrative nursing combined with Traditional Chinese Medicine foot soaking and auricular acupoint pressing in the treatment of post-stroke sleep disorder. Methods From June 2022 to December 2022, 80 patients with sleep disorder after stroke admitted to the Rehabilitation Department of Beijing Longfu Hospital were selected and randomly divided into a control group and a study group, with 40 patients in each group. Patients in the control group received routine nursing intervention, and those in the study group were given narrative nursing combined with Traditional Chinese Medicine foot soaking and auricular acupoint pressing in addition to the routine nursing. Pittsburgh Sleep Quality Index(PSQI) scale was used to measure patient’s sleep quality. Hamilton Anxiety Scale (HAMA) and Hamilton Depression Scale (HAMD) were performed to evaluate the patient’s anxiety and depression level. Results The PSQI score was decreased in both two groups after intervention, and PSQI score in the study group was lower than that in the control group (P＜0. 01). The HAMA and HAMD scores were decreased in both two groups after intervention, and HAMA and HAMD scores in the study group were lower than that in the control group (P＜0. 01). Conclusion The narrative nursing combined with Traditional Chinese Medicine foot soaking and auricular acupoint pressing can effectively improve the sleep quality of stroke patients with sleep disorder. (目的 探讨叙事护理联合中药泡足和耳穴贴压治疗脑卒中后睡眠障碍的效果。方法 2022年6月—12月, 选取北京市隆福医院康复科收治的脑卒中后睡眠障碍患者80例, 采用随机数字表法分为对照组和研究组, 各40例。对照组患者将接受常规护理干预, 研究组在对照组的基础上接受叙事护理联合中药泡足和耳穴贴压治疗, 采用匹兹堡睡眠质量指数(PSQI)评价患者睡眠质量, 采用汉密尔顿焦虑量表(HAMA)评分和汉密尔顿抑郁量表(HAMD)评分评估患者焦虑和抑郁程度。结果 干预后, 两组PSQI量表总分较干预前下降, 且研究组PSQI量表总分低于对照组, 差异有统计学意义(P＜0. 01)。干预后, 两组HAMA和HAMD量表总分较干预前下降, 且研究组HAMA和HAMD量表总分低于对照组, 差异有统计学意义(P＜0. 01)。结论 叙事护理联合中药泡足和耳穴贴压能有效改善脑卒中后睡眠障碍患者的睡眠质量和负性情绪。)